Correlation of Self-Management Behavior with Blood Pressure in Productive Age Hypertension Patients : Cross-Sectional Study at UPT Puskesmas Mentikan Mojokerto City - Evitasari, Rika Putri; Yuniarti, Enny Virda; Merbawani , Raras (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Hypertension is known as the "silent killer." Patients are expected to actively engage in self-management behavior to reduce symptoms and the risk of complications. This study aimed to determine the relationship between self-management behavior and blood pressure in productive-aged hypertension patients. The method used was a correlational analytic approach with a cross-sectional design, involving 94 respondents out of a total of 102 through purposive sampling. The instruments used were the hypertension self-management behavior questionnaire and a sphygmomanometer. The results showed that 21 respondents (100%) with good behavior had normal blood pressure, 31 respondents (55.4%) with moderate behavior experienced stage 1 hypertension, and 15 respondents (88.2%) with poor behavior were in stage 2 hypertension. Analysis using Spearman's rank showed a p-value of 0.000<0.05 and an r-value of −0.827. In conclusion, there is a negative relationship between self-management behavior and blood pressure: the better the behavior, the lower the blood pressure.